Adsorption of U(VI) on sericite in the presence of Bacillus subtilis: A combined batch, EXAFS and modeling techniques. (1st May 2016) - Sun, Yubing; Zhang, Rui; Ding, Congcong; Wang, Xiangxue; Cheng, Wencai; Chen, Changlun; Wang, Xiangke
Abstract: The effect of Bacillus subtilis ( B. subtilis ) on the adsorption of U(VI) onto sericite was investigated using batch, EXAFS and modeling techniques. The batch adsorption indicated that the increased adsorption of U(VI) on sericite +  B. subtilis systems at pH < 5.0 was predominantly attributed to the formation of inner-sphere complexes between U(VI) and surface functional groups of B. subtilis, whereas the inhibited adsorption was observed at pH > 6.0 due to the combination of deprotonated carboxyl groups of B. subtilis with the hydroxyl of sericite. The slightly enhanced adsorption of U(VI) on sericite +  B. subtilis with increasing CO2 contents at pH < 6.0 was ascribed to the electrostatic attraction between positively charged U(VI) species (UO2 2+ species) and negatively charged surface of sericite +  B. subtilis, whereas the U(VI) adsorption sharply decreased at pH > 7.0 owing to electrostatic repulsion between negatively charged sericite +  B. subtilis and negatively charged U(VI) species such as UO2 (OH)3 − or UO2 (CO3 )2 2 − species. According to EXAFS analysis, the increased adsorption mechanism of U(VI) on sericite +  B. subtilis at pH 4.0 was attributed to the formation of U–P shell, whereas the bidentate inner-sphere surface complexes was also observed at pH 7.0 due to the formation of U–C shell (2.92 Å) and/or U–Si/Al (3.18 Å) shell. Under the range of allowable error, the pH-dependent and isothermal adsorption of U(VI) on sericite +  B. subtilis can be fitted by surface complexation modeling using ion exchange and surface complexation reaction by using equilibrium parameters obtained from each binary systems. These findings are important to understand the fate and transport of U(VI) on the mineral–bacteria ternary systems in the near-surface environment.